2012
DOI: 10.1093/ejo/cjs022
|View full text |Cite
|
Sign up to set email alerts
|

Negative self-perception of smile associated with malocclusions among Brazilian adolescents

Abstract: This study estimated the prevalence of negative self-perception of smile because of occlusion abnormalities and investigated their association according to standard clinical criteria. The sample consisted of 1290 randomly selected Brazilian adolescent boys and girls aged 12-16 years. The outcome of interest was dissatisfaction with smile, and data were collected using a standardized questionnaire. Occlusion characteristics were assessed using the dental aesthetic index (DAI). The other study variables were gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
1
12
0
4
Order By: Relevance
“…Both factors could be relevant in the increasing complexity in managing patient's aesthetic concerns. The use of self-perception in assessing patients' treatment needs has been stressed [15].…”
Section: Introductionmentioning
confidence: 99%
“…Both factors could be relevant in the increasing complexity in managing patient's aesthetic concerns. The use of self-perception in assessing patients' treatment needs has been stressed [15].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, understanding of the health-disease process requires a more contextualized approach that involves issues related to access to health care and decision-making of all those participating in the treatment [24]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated malocclusion, in particular Badran et al [2], Moura et al [4], Farias et al [5], Feu et al [6], Peres et al [7], and Thomaz et al [8], who found several associations. Gender, age, educational level, social status, malocclusion severity, access to dental care, self-perception of facial aesthetics, dentists’ recommendations, concern of parents, and the influence of classmates are commonly associated factors.…”
Section: Introductionmentioning
confidence: 99%
“…Considerando o fator idade, a literatura afirma que 97% das crianças, aos cinco anos de idade, apresentam diastemas 3 , que diminuem grandemente entre nove e onze anos, até os 15 anos de idade. Outros estudos sobre a incidência de diastemas em crianças e adolescentes foram realizados [3][4][5] e, em concordância entre os autores, foi observado que a maior incidência acometia meninos de todas as origens étnicas. Outro ponto em comum é o fator raça, no qual a incidência é maior para os melanodermas, seguido dos leucodermas e por último nos xantodermas.…”
unclassified